Pengaruh Bauran Promosi Terhadap Kepuasan Nasabah Melalui Keputusan Menggunakan Kredit Produktif di Bank Riau Kepri Kedai Sabak Auh - Adriansyah; Gatot Wijayanto; Ando Fahda Aulia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
One of the networks of Bank Riau Kepri Siak Branch is Bank Riau Kepri Sabak Auh shop which is expected to be able to provide productive credit marketing and be able to become a market leader for similar credit products in terms of lower interest rates than other banks. Customers of Bank Riau Kepri Kedai Sabak Auh are retail customers and there is no collaboration with cooperatives or other institutions in terms of offering credit to their members. This is different from other office units in the Bank Riau Kepri Siak network which have cooperation with cooperatives or other institutions in providing productive credit to their members. This study aims to analyze the effect of the promotion mix on the decision to use credit. The effect of the promotion mix on customer satisfaction. The effect of the decision to use productive credit and to analyze the effect of the promotion mix on customer satisfaction through the decision to use credit. The population in this study were all productive credit customers (KUKM and KUM) at Bank Riau Kepri Kedai Sabak Auh in 2021 spread across the Sabak Auh sub-district as many as 161 people. While the sample used as many as 118 people. The data used in this study were primary data and secondary data, while the data collection technique used a questionnaire. The data analysis technique used in this research is the data analysis used in this study is the Structural Equation Model. The results showed that the Promotional Mix had a positive and significant effect on the decision to use credit. Promotional mix has a positive and significant effect on visitor goals. The decision to use has an effect on customer satisfaction. And the promotion mix affects the customer's goals through the decision to use productive credit.